2021
DOI: 10.1016/j.physe.2021.114668
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical studies of the adsorption of Remdesivir, as an effective drug for treatment of COVID-19, on the surface of pristine, COOH-functionalized and S-, Si- and Al- doped carbon nanotubes

Abstract: Remdesivir has been recognized as an important medicine in the control of COVID-19 illness. Since carbon nanotubes were considered in the design of novel drug delivery vehicles, the interaction between simple CNT, functionalized CNT by carboxylic group and S-, Al-, and Si-doped CNT and Remdesivir drug were studied using density functional theory (DFT) and time dependent DFT (TDDFT) calculations. The results of this work show that the Si-doped CNT is the best drug delivery system for Remdesivir due to its bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…In contrast, the neutral zones are shown in light yellow-green color. 82 84 Figure 6 shows the MEP map of the (a) drug (CEX), (b) carrier (GO/PEG), and (c) GO/PEG-CEX complex with an isosurface value is ±0.016e/Å 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the neutral zones are shown in light yellow-green color. 82 84 Figure 6 shows the MEP map of the (a) drug (CEX), (b) carrier (GO/PEG), and (c) GO/PEG-CEX complex with an isosurface value is ±0.016e/Å 3 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the positive regions of electrostatic potential with low electron density, which are illustrated in blue and green, have been linked to nucleophilic reactivity. In contrast, the neutral zones are shown in light yellow-green color. Figure shows the MEP map of the (a) drug (CEX), (b) carrier (GO/PEG), and (c) GO/PEG-CEX complex with an isosurface value is ±0.016e/Å 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Bagheri Novir et al made quantum mechanical studies of the adsorption of Remdesivir®, as an effective drug for the treatment of COVID-19 on the surface of pristine, COOHfunctionalized, and S-, Si-and Al-doped (5,5) SWCNT. Also, they concluded that the Si-doped CNT is the best nano vehicle for Remdesivir® drug delivery compared to the pristine CNT and the other functionalized and doped CNTs investigated in this study because of its better reactivity, better energetic, electronic, adsorption, and thermodynamic properties [21].…”
Section: Introductionmentioning
confidence: 82%
“…The calculated values of ΔH and ΔG were negative for all new complexes at all investigated nanotubes, meaning these new complexes were exothermic and spontaneous. ΔS with negative values indicate that the complex is ordered [44]. That's why the thermodynamic parameters show that the investigated nanotubes are more appropriate by evaluating the thermodynamic stability for Hydroxychloroquine drug delivery.…”
Section: Hydroxychloroquine Adsorption On Sic-ntmentioning
confidence: 98%